2007
DOI: 10.1017/s1751731107000018
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour influences cholesterol plasma levels in a pig model

Abstract: Little is known about the relationship between feed intake behaviour and cholesterol levels in humans. This can be attributed to the fact that feed intake behaviour in humans is difficult to assess. The relationships between feed intake, feed efficiency and feed intake behaviour, and cholesterol and triglyceride levels were investigated at an average age of 187 days, in a pig model consisting of 202 Duroc barrows. Feed intake and feed intake behaviour were recorded individually and daily by means of an electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
23
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 41 publications
6
23
1
Order By: Relevance
“…Circulating lipid indicators were weakly correlated with growth and fatness traits. Rauw et al (2007), also in Duroc, found similar correlations between serum lipids and production traits than in our research. Etherton and Kris-Etherton (1980) showed that plasma-TG, very low density lipoproteins (VLDL), and HDL-C were highly and positively correlated in 1-year old pigs.…”
Section: Tablesupporting
confidence: 87%
See 1 more Smart Citation
“…Circulating lipid indicators were weakly correlated with growth and fatness traits. Rauw et al (2007), also in Duroc, found similar correlations between serum lipids and production traits than in our research. Etherton and Kris-Etherton (1980) showed that plasma-TG, very low density lipoproteins (VLDL), and HDL-C were highly and positively correlated in 1-year old pigs.…”
Section: Tablesupporting
confidence: 87%
“…A possible explanation is that HDL-C and VLDL are metabolically related, for instance, increasing VLDL half-life. Thus, Birchbauer et al (1992) showed that the half-life of VLDL increases by transferring apoE to HDL-C. Several studies observed a positive association between HDL-C and body weight at different ages (Gallardo et al, 2008;Pond et al, 1993;Rauw et al, 2007). In the present study, HDL-C was positively correlated to carcass weight at 120 days but not at 185 days, indicating that this relationship, at least in Duroc, is primarily found at earlier stages of growth.…”
Section: Tablesupporting
confidence: 49%
“…In general, TC showed a highly significant phenotypic correlation with TG, LDL-C and HDL-C, whereas TG showed a significant phenotypic correlation with serum levels of HDL-C and LDL-C. Furthermore, there was a highly significantly positive correlation between serum levels of LDL-C and HDL-C. Our results are very similar to the phenotypic correlations among serum lipids levels reported in a Duroc 9 Pietrain cross-bred population and in Duroc pigs (Rauw et al 2007;Uddin et al 2011).…”
supporting
confidence: 87%
“…However, cholesterol and LDL cholesterol content were significantly higher in the serum of piglets from sows housed in groups (P = 0.006 and 0.005, respectively), and serum glucose also tended to be higher (P = 0.07) in these piglets in the present study. The different cholesterol content may indicate the different food intake behaviour of offspring (Rauw et al, 2007). Similarly, Estienne and Harper (2010) showed that gilts from female sows gestated in groups tended (P < 0.09) to have more back fat than gilts from female sows gestated (c) Figure 3 Effects of stall and group housing on agonistic behaviour duration (line chart) and the frequency of agonistic and non-agonistic behaviour (bar chart) in pregnant sows.…”
Section: Discussionmentioning
confidence: 95%